Utilisation of Aegilops (goatgrass) species to widen the genetic diversity of cultivated wheat - Schneider, Annamária; Molnár, István; Molnár-Láng, Márta (Euphytica, 2008)
Wild Aegilops species related to cultivated wheat ( Triticum spp.) possess numerous genes of agronomic interest and can be valuable sources of resistance to diseases, pests and extreme environmental factors. These genes can be incorporated into the wheat genome via intergeneric crossing, following, where necessary, the development of chromosome addition and substitution lines from the resulting hybrids. The transfer of a single segment from an alien chromosome can be achieved by translocations. The Aegilops (goatgrass) species, which are the most closely related to wheat, exhibit great genetic diversity, the exploitation of which has been the subject of experimentation for more than a century. The present paper gives a survey of the results achieved to date in the field of wheat– Aegilops hybridisation and gene transfer. The Aegilops genus consists of 11 diploid, 10 tetraploid and 2 hexaploid species. Of these 23 Aegilops species, most of the diploids ( Ae. umbellulata Zhuk., Ae. mutica Boiss., Ae. bicornis (Forssk.) Jaub. & Spach, Ae. searsii Feldman & Kislev ex Hammer, Ae. caudata L., Ae. sharonensis Eig, Ae. speltoides Tausch, Ae. longissima Schweinf. & Muschl.) and several polyploids ( Ae. ventricosa Tausch, Ae. peregrina (Hack. In J. Fraser) Marie & Weiller, Ae. geniculata Roth, Ae. kotschyi Boiss., Ae. biuncialis L.) have been used to develop wheat– Aegilops addition lines. Wheat– Aegilops substitution lines were developed using several species, including Ae. umbellulata , Ae. caudata , Ae. tauschii , Ae. speltoides , Ae. sharonensis , Ae. longissima and Ae. geniculata . Translocations carrying genes responsible for useful agronomic traits were developed with Ae. umbellulata , Ae. comosa , Ae. ventricosa , Ae. longissima , Ae. speltoides and Ae. geniculata . A large number of genes were transferred from Aegilops species to cultivated wheat, including those for resistance to leaf rust, stem rust, yellow rust and powdery mildew, and various pests (cereal cyst nematode, root knot nematode, Hessian fly, greenbug). Many molecular markers are linked to these resistance genes. The development of new molecular markers is also underway. There are still many untapped genetic resources in Aegilops species that could be used as resistance sources for plant breeding.